Technology Acceptance Model (TAM), Student Engagement, and Psychological Well-Being in Islamic Education: Evidence from Vocational Schools - Mazrur; Hunainah; Surawan; Fathimatuz Zahra (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The integration of digital technology in education has become increasingly important; however, its effectiveness in Islamic Education remains underexplored, particularly regarding student engagement and psychological well-being. This gap is evident in vocational school contexts, where technology use does not always translate into active participation or positive mental outcomes. Therefore, this study aims to examine the relationships between the Technology Acceptance Model (TAM), student engagement, and psychological well-being in Islamic Education among students in private vocational schools in Palangka Raya City. This study employed a quantitative approach with a cross-sectional survey design. A sample of 250-300 students was selected using stratified random sampling. Data were collected through a structured questionnaire and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings indicate that TAM has a significant positive effect on student engagement and psychological well-being. Student engagement also significantly influences psychological well-being and partially mediates the relationship between technology acceptance and well-being. These results suggest that effective technology integration should promote both usability and active engagement to support students’ psychological well-being. The study contributes to the literature by providing an integrated model in Islamic Education and recommends the development of interactive, student-centred digital learning environments, as well as further longitudinal research.